Who Should be Our Leader? Examining Female Representation in the Principalship Across Geographic Locales in Texas Public Schools - Edward J. Fuller; Andrew Pendola; Marie LeMay (Journal of Research in Rural Education, 2018)
Since the 1970s, there has been keen interest in examining gender representation in leadership positions across various areas of employment, including K-12 education. Indeed, there have been long-standing concerns about the percentage of women principals. Few studies, however, have examined the percentages of women principals at different schooling levels (elementary, middle, and high schools) and across different geographic locales. In this study, we rely on 23 years of employment data for Texas public schools to examine the percentage of employed principals and newly hired principals who were women by school level and geographic locale. We also employ logistic regression to identify the independent effect of a school being located in a rural area on the odds of a school hiring a woman to be principal. We find that schools in all locales evidence an increase in hiring women as principals"particularly during the 1990s. We also find schools located in rural areas"both inside and outside metropolitan statistical areas"were less likely than schools located in large cities and large suburbs to employ a woman principal and hire a woman to fill a vacancy in the principalship.